You are correct until the I think maybe you distributed wrong.
Here,
Hi, I've been working on this problem for a while now and can't seem to figure it out. I know the right answer but I'm having problems getting to it on my own.
Here's the problem: "Find the length of the shorter leg of a right triangle if the longer leg is 3cm more than the shorter leg and the hypotenuse is 6cm more than the shorter leg."
Here is the what I have so far, I know the answer is 9cm but I cannot figure out how they got to that.
Shorter leg = x, longer leg = x+3, hypotenuse = x+6. Using a^{2} + b^{2} = c^{2} I get x^{2} + (x+3)^{2} = (x+6)^{2}
x^{2} + x^{2} + 9 = x^{2} + 36
2x^{2} + 9 = x^{2} + 36
-9 - 9
2x^{2} = x^{2} + 27
-x^{2} -x^{2}
x^{2} = 27 ??????